Treatment of catheter-related thrombosis in patients with hematologic malignancies: A Venous thromboEmbolism Network U.S. retrospective cohort study - Baumann Kreuziger, Lisa; Gaddh, Manila; Onadeko, Oluwatomiloba; George, Gemlyn; Wang, Tzu-Fei; Oo, Thein H.; Jaglal, Michael; Houghton, Damon E.; Streiff, Michael B.; Gali, Radhika; Feng, Mingen; Simpson, Pippa; et al. (Thrombosis research, 2021)
Optimal treatment of catheter-related thrombosis (CRT) is uncertain in patients with hematologic malignancy. We aimed to evaluate the treatment strategies, outcomes, and predictors of recurrent venous thromboembolism (VTE) associated with catheter-related thrombosis (CRT) in patients with hematologic malignancy. We performed a multicenter retrospective cohort study of eight institutions through the Venous thromboEmbolism Network US. Patients with hematologic malignancies with documented CRT were identified using ICD-9 and ICD-10 diagnostic codes. Semi-competing risks proportional hazard regression models were created. Of the 663 patients in the cohort, 124 (19%) were treated with anticoagulation alone, 388 (58%) were treated with anticoagulation and catheter removal, 119 (18%) treated with catheter removal only, and 32 (5%) had neither catheter removal nor anticoagulation. 100 (15%) patients experienced a recurrent VTE event. In the 579 patients who had catheter removal, the most common reason for catheter removal was the CRT [392 (68%)]. For subjects who received any anticoagulation (n = 512), total anticoagulation duration was not associated with VTE recurrence [1.000 (0.999–1.002)]. After adjustment patients treated with catheter removal only had an increased risk of VTE recurrence [2.50 (1.24–5.07)] and death [4.96 (2.47–9.97)]. Patients with no treatment had increased risk of death [16.81 (6.22–45.38)] and death after VTE recurrence [27.29 (3.13–238.13)]. In this large, multicenter retrospective cohort, we found significant variability in the treatment of CRT in patients with hematologic malignancy. Treatment without anticoagulation was associated with recurrent VTE. •Central venous catheters are associated with catheter related thrombosis (CRT).•Completed a retrospective multicenter cohort of CRT and hematologic malignancy•Many catheters were removed due to thrombosis despite anticoagulation.•Recurrent VTE occurred in 15% of patients.•CRT treatment without anticoagulation was associated with increased VTE recurrence.